Generation of Dip2a homozygous knockout murine ES cell line IBMSe001-A-1 via CRISPR/Cas9 technology - Mingze Yao; Qian Yang; Mengqiao Lian; Pengfei Su; Xiaogang Cui; Tinglin Ren; Xiedong Wang; Changxin Wu; Yaowu Zheng (Stem Cell Research, 2020)
DIP2A mutation is associated with abnormal brain development and diseases including dyslexia, autism and Alzheimer's disease. However, the role and the involved mechanisms remain unknown. To study the biological function of DIP2A during mESCs neural differentiation in early neural development, we generated a Dip2a homozygous knockout 46C ESC cell line using CRISPR/Cas9 genome editing technology. The eighth exon of Dip2a gene was replaced with PGK-Puro-P2A-mCherry. This 46C-Dip2a KO cell line offers a useful resource to investigate the molecular mechanisms of DIP2A in the process of cell fate determination, as well as a potential source of building disease mouse model.